Using molecular and crowd‐sourcing methods to assess breeding ground diet of a migratory brood parasite of conservation concern. (18th September 2020) - Mills, Lowell J.; Wilson, Jeremy D.; Lange, Anke; Moore, Karen; Henwood, Barry; Knipe, Hazel; Chaput, Dominique L.; Tyler, Charles R.
Abstract : Breeding ground food availability is critical to the survival and productivity of adult birds. The common cuckoo Cuculus canorus is a brood‐parasitic Afro‐Palearctic migrant bird exhibiting long‐term (breeding) population declines in many European countries. Variation in population trend between regions and habitats suggests breeding ground drivers such as adult food supply. However, cuckoo diet has not been studied in detail since before the most significant population declines in Europe began in the mid‐1980s. 20th century studies of cuckoo diet largely comprised field observations likely to carry bias towards larger prey taxa. Here we demonstrate the potential value of 1) using high‐throughput DNA sequencing of invertebrate prey in faeces to determine cuckoo diet with minimal bias towards large prey taxa, and 2) using crowd‐sourced digital photographs from across Britain to identify lepidopteran cuckoo prey taxa during recent years post‐decline (2005–2016). DNA analysis found a high frequency of Lepidoptera, including moths of family Lasiocampidae, prominent within the past literature, but also grasshoppers (Orthoptera) and flies (Diptera) that may be overlooked by field observation methodologies. The range of larval lepidopteran prey identified from photographs largely agreed with those previously documented, with potential signs of reduced diversity, and identities of key adult prey taxa were supported by molecular results. Notably, many identified cuckoo prey taxa have shown severe declines due to agricultural intensification, suggesting this has driven spatial patterns of cuckoo loss. Landscape‐scale, lowland rewilding interventions provide opportunities to understand the scale of reversal of previous agricultural intensification that may be necessary to restore prey populations sufficiently to permit recolonization by cuckoos.